If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) = x + -4 Reorder the terms: 2(-1 + x) = x + -4 (-1 * 2 + x * 2) = x + -4 (-2 + 2x) = x + -4 Reorder the terms: -2 + 2x = -4 + x Solving -2 + 2x = -4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2 + 2x + -1x = -4 + x + -1x Combine like terms: 2x + -1x = 1x -2 + 1x = -4 + x + -1x Combine like terms: x + -1x = 0 -2 + 1x = -4 + 0 -2 + 1x = -4 Add '2' to each side of the equation. -2 + 2 + 1x = -4 + 2 Combine like terms: -2 + 2 = 0 0 + 1x = -4 + 2 1x = -4 + 2 Combine like terms: -4 + 2 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| -8x+5y=7 | | x(2)-x=0 | | 2x^2+3x-7=x^2+5x+39 | | 3(p+9)-12p=51 | | 6-6x+3x=-21 | | 11p=22 | | 5x+10+11x+2+58=360 | | 4x^2+5x=-12 | | 12(m+20)=16m | | x(2)+5x-14=0 | | 8w-30=5w-40 | | 4x^2=-12x-6 | | (x/4)=(x/5)+(7/4) | | 2y-1/21=3y-7/15 | | 10+x+60=90 | | 10=2(2x-1) | | -0.08y+0.10(800-y)=0.07y | | 3x/x+2-x/x-2+8/x^2-4 | | 3x=x+10+2 | | 1/2x-3=-2 | | 4+10m-5+2m=1 | | 3x/x+2-x/x-2+8/x2-4 | | 3/5x-1=5 | | n(2)=-8n-7 | | 2/7x+8=0 | | 2n^2+6n=108 | | -7x-6=-6 | | 3(x-3)+6=-4+x-23 | | 15-1/5x=5 | | 2(2x+2)=12 | | -6x-6=-6 | | 8-1/4x=-4 |